Statistics: general linear models (a flexible approach). (19th August 2014) - Scott, M.; Flaherty, D.; Currall, J.
<x xml:space="preserve">Abstract</x> This article moves on to discuss a type of statistical testing different from those we have discussed previously, namely a General Linear Model. This system incorporates a number of other statistical models and is a powerful tool used widely in modern statistics.